2016
DOI: 10.1039/c6ay00782a
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of urine, oral fluid and fingerprints by liquid extraction surface analysis coupled to high resolution MS and MS/MS – opportunities for forensic and biomedical science

Abstract: Liquid Extraction Surface Analysis (LESA) is a new, high throughput tool for ambient mass spectrometry. A solvent droplet is deposited from a pipette tip onto a surface and maintains contact with both the surface and the pipette tip for a few seconds before being re-aspirated. The technique is particularly suited to the analysis of trace materials on surfaces due to its high sensitivity and low volume of sample removal. In this work, we assess the suitability of LESA for obtaining detailed chemical profiles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…Although LESA mass spectrometry has been widely applied to the analysis of small molecules (eg, drugs and their metabolites), comparatively few reports describe intact protein analysis from tissue. Schey et al applied manual LESA extraction to sections of bovine ocular lens and mouse brain and kidney.…”
Section: Ambient In Situ Analysis Of Intact Proteins In Biological Sumentioning
confidence: 99%
“…Although LESA mass spectrometry has been widely applied to the analysis of small molecules (eg, drugs and their metabolites), comparatively few reports describe intact protein analysis from tissue. Schey et al applied manual LESA extraction to sections of bovine ocular lens and mouse brain and kidney.…”
Section: Ambient In Situ Analysis Of Intact Proteins In Biological Sumentioning
confidence: 99%
“…A LESA extraction solvent was prepared containing methanol, water, and formic acid in a volume ratio of, respectively, 70:30:0.1. 3 Slides were placed onto the LESA universal plate holder and scanned with an Epson V300 scanner, and coordinates of sample locations were selected with LESA Points software (Advion Biosciences, Inc., Ithaca, USA). After that, LESA was performed using the TriVersa Nanomate (Advion Biosciences, Inc., Ithaca, USA).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…L iquid extraction surface analysis−mass spectrometry (LESA-MS) is an ambient mass spectrometry technique in which analytes are extracted from a surface by the formation of a liquid microjunction between the extraction solvent and the surface. 1 This technique has already been widely applied for the analysis of proteins, 2 metabolites, 3 drugs, 3 and lipids 4 in a wide range of matrices and on various surface substrates. One of the main limitations of LESA-MS is poor repetitive sampling due to spreading of the probe solvent on the surface of interest.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…Its ease of use, reproducibility, automated functionality, and ability to interrogate discrete regions of a sample have been demonstrated for the analysis of several classes of biomolecules from a range of surfaces, including tissue, dried blood spots, food surfaces, and latent fingerprints . Previous studies have shown the capabilities and application of LESA, which utilized disposable capillary tips and enabled offline proteomics analysis of tissue extracts . Recently, this liquid extraction technology has been modified by replacing the disposable capillary with a glass capillary (LESAplus) allowing for increased droplet resolution on the sample surface.…”
Section: Introductionmentioning
confidence: 99%